Elite retweets, opinions and engagement: the use Twitter by South African journalist Barry Bateman - Granger, Lauren Claire (Centre for Film and Media Studies, 2014)
This study examines how Twitter is used by South African journalist Barry Bateman to share news, report from events and communicate with his audience for two months (from 13 May to 13 July 2013). Content analysis and social network analysis are used to investigate the tweets, the responses he receives and discussions he is involved with on the social network site. While Bateman uses his Twitter account primarily to share the posts of other professional journalists and to promote his own work, organisation and colleagues, he also answers individual questions from users, going beyond the uni-directional model of journalism to engage in conversations and share resources. Bateman's use of Twitter also raises questions about how journalists negotiate the boundaries of the personal and professional on a medium where posting opinion is the norm, and how individuals with influence on the social network site can help 'the rich get richer' by highlighting other popular and powerful users.